North Atlantic euphotic ocean temperatures derived from coccolith clumped isotopes and alkenones from ODP Site 162-982 since the Miocene (1.99-16 Ma) - Luz María Mejía; Stefano M Bernasconi; Alvaro Fernandez; Hongrui Zhang; José Guitián; Madalina Jaggi; Victoria E Taylor; Alberto Perez-Huerta; Heather M Stoll (PANGAEA, 2025)
Accurate predictions of the future climate response to CO2 depend on the ability of climate models to simulate past analog warmer climates, like the Miocene. However, one key unresolved issue in paleoclimate modeling is reproducing the pronounced high-latitude warmth and relatively flat latitudinal temperature gradients inferred from proxy records. Here, we use clumped isotope thermometry—a method that sidesteps limitations of conventional proxies—on pure coccolith calcite from the high-latitude North Atlantic ODP Site 982, extending from the Mid Miocene to the Quaternary (16-1.99 Ma; 524.55-43.99 m (mcd)), and compare to alkenone-derived temperatures from the same samples. We also measured clumped isotopes from a sediment trap sample from the Iceland Sea (70.23° N; 9.75° W; 1884 m) which in July 1999 registered the largest surface bloom ever recorded in this area, containing 99% of the subpolar north Atlantic Coccolithus pelagicus. The ketone fraction from bulk ODP Site 982 samples was extracted via Accelerated Solvent Extraction (ASE) and purified using saponification and silica gel column chromatography, after which C37:2 and C37:3 were measured at ETH Zürich using a Thermo Scientific Trace 1310 Gas Chromatograph (GC) coupled to a flame ionization detector. Alkenone SSTs were then calculated using widely-available calibrations like the core top (Müller et al., 1998; doi:10.1016/S0016-7037(98)00097-0), the 55a Emiliania huxleyi batch culture (Prahl et al., 1988; doi:10.1016/0016-7037(88)90132-9) and the BAYSPLINE (Tierney and Tingley, 2018; doi:10.1002/2017PA003201), and alkenone production temperatures accounting for season and depth of production were calculated using the calibration proposed in Mejia et al., (2023; doi:10.1016/j.epsl.2023.118313). Coccoliths from the inorganic ODP Site 982 samples were then purified using centrifugation and microfiltering techniques as described in Mejia et al., (2025; doi:10.21203/rs.3.rs-6393158/v1). Any further organic components were eliminated by H2O2 oxidation to avoid interferences during clumped isotope analysis. Clumped isotopes were measured from purified downcore samples and the sediment trap using a Kiel IV-Thermo Scientific MAT 253 at ETH Zürich. Coccolith calcification temperatures were calculated using the latest coccolith clumped isotope culture calibration study (Clark et al., 2024; doi:10.5194/cp-20-2081-2024) and the foraminifera calibration of Meinicke et al., (2021, doi:10.1029/2020PA004115).